A new species of Balera Young and redescription of Habralebra gillettei Young (Hemiptera, Cicadellidae, Typhlocybinae) from Viçosa, Minas Gerais State, Brazil - Coelho, Luci Boa Nova (Zootaxa, 2013)
Balera fiuzai sp. nov. is described based on male specimens obtained from light trap collections at Mata do Paraíso, Mu-nicipality of Viçosa, Minas Gerais State, Brazil. An identification key to the species of Balera is given. Additionally, Habralebra gillettei Young is redescribed from the same locality. These specimens of H. gillettei differ somewhat from previously described specimens, but are considered intra-specific variations. Both genera, Balera Young and Habralebra Young, are recorded from Minas Gerais State for the first time.